Conflicts between parent company and non-controlling shareholders in stakeholder-oriented corporate governance: evidence from Japan - Fujita, Kento; Yamada, Akihiro (Journal of Business Economics and Management, 2022)
When a company establishes subsidiaries with capital provided by a third party, the subsidiaries’ shareholders include the parent company (controlling shareholders) and minority (noncontrolling) shareholders. When shareholders’ interests are divergent, conflicts may arise, causing inefficiencies in the management of the subsidiaries or the corporate group. Such conflicts among shareholders are called principal–principal (PP) conflicts. However, adopting stakeholder-oriented corporate governance, a practice prevalent in Japan, may mitigate such PP conflicts. In fact, many Japanese companies report non-controlling interests in their consolidated financial statements. This paper investigates the influence of PP conflicts in Japanese corporate groups. The availability of nonconsolidated and consolidated financial statements in Japan allows for the comparison of parent companies’ data with those of the corporate group. The results reveal that (1) the larger the minority shareholders ratio (MER), the more the profits shifted to the parent company, and (2) the larger the MER, the higher the growth of the subsidiaries’ sales rates. These results suggest that while the parent company exploits the non-controlling shareholders through profit shifting, it also allocates sales growth opportunities to subsidiaries to mitigate PP conflicts.